PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI ACEH - Mufti, Fajar; Fadhlia, Wida; Ikhsan, Adhisyahfitri Evalina (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to analyze the disclosure of local government financial statements in District and City Governments in Aceh Province based on regional autonomy, intergovernmental revenue, and legislative size on report disclosure. The population of this study is the District and Municipal Government Financial Statements in Aceh Province from 2017 to 2021. The data used in this study are secondary data derived from Local Government Financial Statements. The analysis method used is multiple linear regression which is processed using the SPSS version 25 application. The results showed that regional autonomy, balanced funds, and legislative size simultaneously affected the disclosure of local government financial statements. Partially, regional autonomy and intergovernmental revenue affect the disclosure of local government financial statements, while legislative size does not affect the disclosure of local government financial statements. In addition, to expand the research results, further research is recommended to employ other variables such as population, number of SKPD, and total assets.